2022
DOI: 10.1557/s43578-022-00767-z
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion irradiation-induced amorphous iron and Fe–Si oxide phases in metallic 57Fe layer vacuum deposited on surface of SiO2/Si

Abstract: Abstract57Fe conversion electron Mössbauer (CEM) spectroscopy, SEM and magnetization measurements were used to study the effect of swift heavy ion irradiation on metallic 57Fe (10 nm) thin layer vacuum deposited onto SiO2/Si. About 85% of the total iron content of the surface layer detected by CEM was present as metallic, crystalline alpha iron before the irradiation, while upon irradiation with 160 MeV Xe ions, with a fluence of 5 × 1013 ion cm−2, ~ 21% was converted to amorphous iron and ~ 47% to silicon-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…In the case of 155 MeV Xe ion irradiation with the higher fluence of 1 × 10 14 ion cm −2 , an even larger amount, 31 × 10 18 vacancies, were created in the nano-maghemite, which could induce an even stronger effect, creating a much larger amount of irradiation-induced superparamagnetic region than in the case of the lower fluence irradiation. The results we obtained for the fluence threshold were consistent with those reported for different oxides [36,43,49,50,68,69,73,74] taking into account the difference in the irradiation parameters. The electron stopping power in our case far exceeded the 6 keV nm −1 threshold for dislocation formation estab-lished by Khara et al [39], who developed a computer model to estimate dislocation formations created by swift heavy ion irradiation, which strongly confirmed that we had a suitable amount of dislocations forming new grain boundaries resulting in increased amounts of superparamagnetic regions with fluence in nano-maghemite upon the irradiation.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In the case of 155 MeV Xe ion irradiation with the higher fluence of 1 × 10 14 ion cm −2 , an even larger amount, 31 × 10 18 vacancies, were created in the nano-maghemite, which could induce an even stronger effect, creating a much larger amount of irradiation-induced superparamagnetic region than in the case of the lower fluence irradiation. The results we obtained for the fluence threshold were consistent with those reported for different oxides [36,43,49,50,68,69,73,74] taking into account the difference in the irradiation parameters. The electron stopping power in our case far exceeded the 6 keV nm −1 threshold for dislocation formation estab-lished by Khara et al [39], who developed a computer model to estimate dislocation formations created by swift heavy ion irradiation, which strongly confirmed that we had a suitable amount of dislocations forming new grain boundaries resulting in increased amounts of superparamagnetic regions with fluence in nano-maghemite upon the irradiation.…”
Section: Resultssupporting
confidence: 91%
“…The observed changes due to irradiation could be related to the accelerated diffusion of defects and ions via the molten tracks and ion beam mixing, similarly as reported in other works [43,68,69]. This theory also satisfactorily explained the results [49,50] obtained on other systems irradiated under the same irradiation conditions as the current one.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Swift heavy ions (SHI) are well known to modify characteristics of the materials (Kuzmann et al, 2023;Wu et al, 2023) and devices such as spintronics (Singh et al, 2016;Zhao et al, 2019), electronic (Bharathi et al, 2016; and sensing (Ramola et al, 2022). These ions have the potential to design ferrites for spintronic (Garg et al, 2023) and gas sensing applications (Bagwan et al, 2022).…”
Section: Swift Heavy Ionsmentioning
confidence: 99%